(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The value of food far outweighs the nutritional or taste aspects that often first come to mind. Food represents the identity and unique culture of people and is a way of communicating one’s own identity to others. It serves as a repository of the history and cultural heritage of a people, telling stories and highlighting specificities that otherwise might be missed. Food has been studied from various aspects and is a multi-disciplinary phenomenon. This paper attempts to highlight some characteristics of Mizo food practices, at once similar to food practices of the larger North-east Indian region and yet simultaneously, with particularities that mark its difference from other cuisines.